Corporate Performance Management Best Practices : A Case Study Approach to Accelerating CPM Results - Paladino, Bob, 1959- (Hoboken John Wiley, 2013)
Business improvement best practices and a proven methodology for improving corporate performance management, illustrated through a high performing program including numerous team case studies Corporate performance management consists of a set of processes that help organizations optimize their business performance.
Include Index
Keywords: Management -- Organizational effectiveness -- Performance--Management